US Vicarious Liability of Parents for Copyright Infringement by Minors: Review and Reform - Najafi, Hamed (Frontiers in Law, 2025)
Vicarious liability is one of the types of responsibilities arising from the acts of others. In US law, there are general rules that, if the persons under the control, commit copyright infringement and a financial benefit reach to the person with the right of control, the latter will have a vicarious liability. Undoubtedly, minors are one of the most obvious examples of people under control, which is often done by their parents. Moreover, in the current era, it is very likely that many infringements are committed by minors, especially in the Internet environment. Therefore, parents are generally subject to vicarious copyright liability arising from the infringing acts minors. the probability of vicarious liability of Parents for chides copyright infringement, has been given under general rule of this type of liability, while the nature of the relationship between parents and children and the basis of parents’ responsibility for the fault of their children, Requires some differences in this regard.